The Law of Recency: An Episodic Stimulus-Response Retrieval Account of Habit Acquisition - Giesen, Carina G.; Schmidt, James R.; Rothermund, Klaus (Frontiers in Psychology, 2020)
A habit is a regularity in automatic responding to a specific situation. Classical learning psychology explains the emergence of habits by an extended learning history during which the response becomes associated to the situation (learning of stimulus-response associations) as a function of practice (“law of exercise”) and/or reinforcement (“law of effect”). In this paper, we propose the “law of recency” as another route to habit acquisition that draws on episodic memory models of automatic response regulation. According to this account, habitual responding results from (a) storing stimulus-response episodes in memory, and (b) retrieving these episodes when encountering the stimulus again. This leads to a reactivation of the response that was bound to the stimulus (c) even in the absence of extended practice and reinforcement. As a measure of habit formation, we used a modified color-word contingency learning (CL) paradigm, in which irrelevant stimulus features (i.e., word meaning) were predictive of the to-be-executed color categorization response. The paradigm we developed allowed us to assess effects of global CL and of an instance-based episodic response retrieval simultaneously within the same experiment. Two experiments revealed robust CL as well as episodic response retrieval effects. Importantly, these effects were not independent: Controlling for response retrieval effects eliminated effects of CL, which supports the claim that habit formation can be mediated by episodic retrieval processes, and that short-term binding effects are not fundamentally separate from long-term learning processes. Our findings have theoretical and practical implications regarding (a) models of long-term learning, and (b) the emergence and change of habitual responding.